Discerning and explaining shape variations in Later Stone Age tanged arrowheads, southern Africa - Smeyatsky, Ilan Ryan (My University, 2017)
Over the past decade a new method of statistical shape analysis, geometric morphometrics, has been applied to the study of artefact shapes. Later Stone Age (LSA) tanged stone arrowheads, hypothesized to act as stylistic markers among prehistoric southern African hunter-gatherer groups, have been analysed with geometric morphometrics and reveal spatially coherent variations in their shape. After being tested against several variables that may have had an effect on arrowhead shape, these stylistic spatial variations could very well indicate large scale linguistic or other kinds of boundaries between different elements of prehistoric San populations. Understanding them can shed light on the social and economic organization of southern African hunter-gatherers during the later Holocene.
A dissertation submitted in fulfilment of the requirements for the Degree of Master of Science in Archaeology of the University of Witwatersrand in 2017.
Keywords: Morphology--Statistical methods; Antiquities; Stone age--Africa, Southern; Hunting and gathering societies--Africa, Southern